Catalytic Asymmetric Conjugate Addition of Indolizines to α, β‐Unsaturated Ketones. Issue 27 (1st June 2017) - Correia, José Tiago Menezes; List, Benjamin; Coelho, Fernando
Abstract: A catalytic enantioselective conjugate addition of indolizines to enones is described. The chiral phosphoric acid ( S )‐TRIP activates α, β‐unsaturated ketones, thereby promoting an enantioface‐differentiating attack by indolizines. Using this reaction, several alkylated indolizines were synthesized in good yields and with enantiomeric ratios of up to 98:2. Abstract : Alkylated indolizines : Using ( S )‐TRIP as monofunctional catalyst, several alkylated indolizines were synthesized in good yields and with enantiomeric ratios of up to 98:2.